Is there a causal relationship between vitamin D and melanoma risk? A Mendelian randomization study. (11th September 2019) - Liyanage, U.E.; Law, M.H.; ,; Barrett, J.H.; Iles, M.M.; MacGregor, S.
Summary: Background: Several preclinical studies have identified the antiproliferative effects of 25‐hydroxyvitamin D [25(OH)D; vitamin D]. Ultraviolet radiation (UVR) is essential for vitamin D synthesis yet increases the risk of melanoma. Observational studies on the association of vitamin D levels with melanoma risk have reported inconclusive results, and are difficult to interpret owing to the potential confounding from the dual role of UVR. Objectives: To determine whether there is a causal association between genetically predicted 25(OH)D concentrations and melanoma using a Mendelian randomization (MR) approach. Methods: We performed MR using summary data from a large genome‐wide association study (GWAS) meta‐analysis of melanoma risk, consisting of 12 874 cases and 23 203 controls. Five single nucleotide polymorphisms associated with 25(OH)D concentration – rs12785878, rs10741657, rs2282679, rs6013897 and rs116970203 – were selected as instrumental variables. An inverse variance weighted method was used to access the evidence for causality. MR results from the melanoma meta‐analysis were combined with results from an MR study based on a melanoma risk GWAS using UK Biobank data. Results: A 20 nmol L −1 decrease in 25(OH)D was not associated with melanoma risk [odds ratio (OR) 1·06, 95% confidence interval (CI) 0·95–1·19]. Results from the UK Biobank were concordant with this, with meta‐analysis of our and UK Biobank‐derived MR causal estimates showing no association (OR 1·02, 95% CI 0·92–1·13 for a 20 nmol L −1 decrease). Conclusions: The results suggest that vitamin D levels may not be causally associated with the risk of melanoma. What's already known about this topic? Antitumour activity of vitamin D has been identified in preclinical studies. Observational studies link vitamin D deficiency with an increased risk of a range of cancers. There is a growing public interest for vitamin D supplementation. Observational studies of melanoma are fraught with difficulties because while higher ultraviolet radiation levels increase vitamin D levels, such exposure is also associated with increased melanoma risk. Results from observational studies are inconclusive regarding the effect of vitamin D on melanoma risk. What does this study add? Using Mendelian randomization, an approach to causal inference, which is analogous to a natural randomized controlled trial, we found no causal association between vitamin D levels and melanoma. Abstract : Plain language summary available online Linked Comment: Bell. Br J Dermatol 2020; 182 :13–14 .